ANALSIS LAPORAN KEUANGAN BERBASIS STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK (SAK ETAP) PADA USAHA MIKRO KECIL MENENGAH (UMKM) DI KELURAHAN AIR PUTIH SAMARINDA - -, Dewi Kuswandi (EKONOMIA, 2017)
The purpose of research is to analyze and compare the financial statements of SMEs Yoga Shop in the Village Water Samarinda with the provisions of SAK ETAP particularly in terms of covering the recognition and measurement of financial statements in the form on the Balance Sheet and Income Statement.Testing the truth of the hypothesis used comparative methods of analysis tools with which to conduct the recognition and measurement of financial statements of the Balance Sheet and Income Statement prepared SMEs Yoga Shop in the Village Water Samarinda Financial Statements according to (SAK ETAP).On the whole of the analysis and discussion it can be concluded that the recognition and measurement in financial statements on MSMEs Shop Yoga in the village of White Samarinda not in accordance with the provisions of Â Â 2009 chapter 2 paragraph 24 (for recognition) and Chapter 31 (for measurement) case this dikarenaka entity does not recognize the post - post fixed assets in the presentation of balance sheet that does not recognize depreciation akumuluasi burden on the presentation of the income statement as well as the measurement of the assets are measured in accordance acquisition costs that can not be measured fixed asset depreciation expense each year.